Multiple hypointense vessels on susceptibility-weighted imaging predict early neurological deterioration in acute ischaemic stroke patients with severe intracranial large artery stenosis or occlusion receiving intravenous thrombolysis. Issue 4 (24th June 2020) - Liu, Yong-Lin; Yin, Han-Peng; Qiu, Dong-Hai; Qu, Jian-Feng; Zhong, Huo-Hua; Lu, Zhi-Hao; Wang, Fang; Liang, Man-Qiu; Chen, Yang-Kun
Abstract : Background and purpose: Early neurological deterioration (END) is a common feature in patients with acute ischaemic stroke (AIS) receiving thrombolysis. This study aimed to investigate whether the presence of multiple hypointense vessels (MHVs) on susceptibility-weighted imaging (SWI) could predict END in patients with the anterior circulation AIS treated with recombinant tissue plasminogen activator (r-tPA). Methods: This was a retrospective study focusing on AIS patients suffering from symptomatic stenosis or occlusion of the middle cerebral artery or internal carotid artery with r-tPA treatment. We collected clinical variables and initial haematological and neuroimaging findings. MHVs were measured on SWI performed after intravenous thrombosis and were defined as the presence of a greater number of veins or veins of a larger diameter with greater signal loss on SWI than those of the contralesional haemisphere. The degree of hyperintensity of MHVs was classified into four grades: none, subtle, moderate and extensive. END was defined as an increase in the National Institutes of Health Stroke Scale score by 2 points during the first 48 hours after the onset of symptoms. Multivariate logistic regressions were conducted to investigate the predictors of END. Results: The study included 61 patients (51 males and 10 females) with a mean age of 62.4±12.6 years. Thirty-five (57.4%) patients presented with MHVs: 8 (13.1%) were graded as subtle MHVs, while 23 (37.7%) and 4 (6.6%) were graded as moderate or extensive MHVs, respectively. Twenty patients (32.8%) presented with END. Logistic regression analysis showed that compared with patients without MHVs, moderate MHVs (adjusted OR 5.446, 95% CI 1.360 to 21.800; p=0.017) and extensive MHVs (adjusted OR 15.240, 95% CI 1.200 to 193.544; p=0.036) were significantly associated with END. Conclusions: MHVs might be a useful predictor of END in AIS patients with symptomatic large artery stenosis or occlusion after r-tPA treatment.